Long Pentraxin-3 Modulates the Angiogenic Activity of Fibroblast Growth Factor-2 - Presta, Marco; Foglio, Eleonora; Churruca Schuind, Ander; Ronca, Roberto (Frontiers in Immunology, 2018)
Angiogenesis, the process of new blood vessel formation from pre-existing ones, plays a key role in various physiological and pathological conditions. Alteration of the angiogenic balance, consequent to the deranged production of angiogenic growth factors and/or natural angiogenic inhibitors, is responsible for angiogenesis-dependent diseases, including cancer. Fibroblast growth factor-2 (FGF2) represents the prototypic member of the FGF family, able to induce a complex “angiogenic phenotype” in endothelial cells in vitro and a potent neovascular response in vivo as the consequence of a tight cross talk between pro-inflammatory and angiogenic signals. The soluble pattern recognition receptor long pentraxin-3 (PTX3) is a member of the pentraxin family produced locally in response to inflammatory stimuli. Besides binding features related to its role in innate immunity, PTX3 interacts with FGF2 and other members of the FGF family via its N-terminal extension, thus inhibiting FGF-mediated angiogenic responses in vitro and in vivo. Accordingly, PTX3 inhibits the growth and vascularization of FGF-dependent tumors and FGF2-mediated smooth muscle cell proliferation and artery restenosis. Recently, the characterization of the molecular bases of FGF2/PTX3 interaction has allowed the identification of NSC12, the first low molecular weight pan-FGF trap able to inhibit FGF-dependent tumor growth and neovascularization. Aim of this review is to provide an overview of the impact of PTX3 and PTX3-derived molecules on the angiogenic, inflammatory and tumorigenic activity of FGF2 and their potential implications for the development of more efficacious anti-FGF therapeutic agents to be used in those clinical settings in which FGFs play a pathogenic role.